Comparison of various SYSADOA for the osteoarthritis treatment: an experimental study in rabbits - Permuy, María (BMC Musculoskelet Disord, 2015)
BACKGROUND: Osteoarthritis is thought to be the most prevalent chronic and disabling joint disease in animals and humans and its treatment is a major orthopaedic challenge because there is no ideal drug treatment to preserve joint structure and function, as well as to ameliorate the symptomatology of the disease. The aim of the present study was to assess, using histology, histomorphometry and micro-CT, the effects of the treatment with several drugs of the SYSADOA group and a bisphosphonate in a model of early osteoarthritis, comparing all the results obtained. METHODS: Osteoarthritis was surgically induced by anterior cruciate ligament transection and partial meniscectomy on one knee of 56 rabbits; treatment was started three weeks after surgery and lasted 8 weeks; at the end of this period, the animals were sacrificed. Animals were divided into seven groups (8 animals each), one for each regimen of treatment (glucosamine sulfate, chondroitin sulfate, hyaluronic acid, diacerein, risedronate and a combination of risedronate and glucosamine) and one for the control (placebo-treated) group. Following sacrifice, femoral osteochondral cylinders and synovial membrane samples were obtained for their evaluation by qualitative and quantitative histology and micro-CT. RESULTS: The model induced osteoarthritic changes in the knee joints and none of the treatments showed a significantly better efficacy over the others. Regarding cartilage thickness and volume, all the treatments achieved scores halfway between control groups, without statistical differences. Regarding the synovial membrane, diacerein and risedronate showed the best anti-inflammatory profile, whereas glucosamine and chondroitin did not present any effect standing the hyaluronic acid results between the others. Regarding the subchondral bone, there were no differences in thickness or volume, but risedronate, diacerein and hyaluronic acid seemed to have considerably modified the orientation of the trabecular lattice. CONCLUSIONS: Out of the different drugs evaluated in the study for OA treatment, diacerein and risedronate showed, in all the parameters measured, a better profile of effectiveness; hyaluronic acid ameliorated cartilage swelling and promoted bone formation, but with a poor synovial effect; and finally, chondroitin and glucosamine sulfate prevented cartilage swelling in a similar way to the others, but had no effect on cartilage surface, synovial membrane or subchondral bone.